Social innovation and strategic knowledge management processes: a critical conceptual overview - Jali, Muhamad Nizam; Abas, Zakaria; Ariffin, Ahmad Shabudin; Baluch, Nazim Hussain (2016)
This paper conceptually explores social innovation as a new innovation outcome strategy and its association with strategic knowledge management processes.The result of this paper found that social innovation is an outstanding solution in addressing social and economic issues highlighted above, because the outcome of social innovation encompasses social, economic and technological payoffs concurrently.Furthermore, this paper highlights strategic knowledge management processes, creates superior knowledge resource that is regarded as a new and novel solution that can be embedded into products, processes and services which in turn leads to the outcome of improving the quality and quantity of people’s life, stimulate economic growth and enhancing technological advances i.e. social innovation. Finally, this paper concludes that social innovation and strategic knowledge management processes must be seriously considered by the policy makers, private sectors and also public institutions given the massive contribution that it might afford to many nations’ core aspirations